Åbningen af et filosofisk rum – Interview med Slavoj Žižek - Daly, Glyn (Slagmark - Tidsskrift for idéhistorie, 2018)
In this interview with Glyn Daly, Slavoj Žižek talks about the birth of ‘The Society for Theoretical Psychoanalysis’, and his own overall philosophical approach. He touches upon his intellectual relationship to thinkers such as Martin Heidegger, Jacques Derrida, Immanuel Kant and of course Jacques Lacan. His sources of inspiration are not only these great theorists, but also his four year long day job as a minute taker for the Yugoslavian communist party, and his personal relationship to Jacques-Alain Miller who gives him his psychoanalytical upbringing. Oversat af Nicklas Weis Damkjær